Synthesis, LIFDI Mass Spectrometry and Reactivity of Triacyl‐Germenolates. Issue 30 (22nd July 2021) - Drusgala, Manfred; Linden, Mathias H.; Knoechl, Andreas; Torvisco, Ana; Fischer, Roland C.; Bernhard Linden, H.; Haas, Michael
Abstract: The synthesis of stable triacylgermenolates 3  a, b was achieved by using a multiple silyl abstraction methodology. The formation of these new germenolates was confirmed by NMR spectroscopy and UV‐Vis measurements. Moreover, for the triacylgermenolates 2 and 3  a LIFDI mass spectrometry to characterize these new compounds. Germenolates 3  a, b serve as a starting point for a new triaacylgermane 4  a and two octaacyldigermanes 4  c, d . The formation of these acylgermanes was confirmed by NMR spectroscopy, X‐ray crystallography, UV‐Vis measurements and mass spectrometry. The UV‐Vis absorption spectra of 4  c, d show considerably increased band intensities due to the presence of eight chromophores. Abstract : New Germenolates. A multiple silyl abstraction pathway was used to isolate two new germenolates. Their formation was confirmed by NMR spectroscopy, UV−Vis measurements as well as LIFDI mass spectrometry was used to exclude any radical side products. These germenolates serve as a starting point for new acylgermanes.